Black pilgrimage to Islam - Dannin, Robert, 1952- (Oxford University Press, 2002)
This book offers a comprehensive ethnographic study of African-American Muslims. Drawing on hundreds of interviews conducted over a period of several years, Dannin provides an unprecedented look inside the fascinating and little understood world of black Muslims. He discovers that the well-known and cult-like Nation of Islam represents only a small part of the picture. Many more African-Americans are drawn to Islamic orthodoxy, with its strict adherence to the Qur'an. Dannin takes us to the First Cleveland Mosque, the oldest continuing Muslim institution in America, on to a permament Muslim village in Buffalo, and then inside New York's maximum-security prisons to hear testimony of the powerful attraction of Islam for individuals in desperate situations. He looks at the aftermath of the assassination of Malcolm X, and the ongoing warfare between the Nation of Islam and orthodox Muslims. Accessibly written, filled with gripping first-hand testimony, and featuring superb illustrations by photographer Jolie Stahl, this book will be the best available guide to the beliefs and culture of African-American Muslims. -- Publisher description.